Estimating nutritive values of Jasminum fruticans L. plant species in northern rangelands of Golestan province. (28th May 2017) - Hosseini, Seyed Ali; Mirdeilami, Seydeh Zohreh; Ghilishli, Fatemeh; Pessarakli, Mohammad
ABSTRACT: Information on different rangeland plants' nutritive values on different plant parts and for various habitats is important in rangelands management. Effects of different plant parts (stems and leaves) of the Jasminum fruticans L. plant species on forage quality indicators were investigated in two regions in 2015. Plant samples were collected from Sharlogh rangelands and cultivated in the Research and Education Center of Agricultural and Natural Resources (RECANR) in Iran with completely randomized design with three replications in each plant sample. The plant leaves and stems samples were oven-dried at 80°C for 24 hr, and then analyzed for crude protein (CP), crude fiber (CF), dry matter (DM), ether extract (EE), crude ash (CA), metabolizable energy (ME), and mineral elements, including calcium (Ca) and phosphorus (P). Results showed that the forage quality indicators in different regions were statistically significant, except for the CA. Also, nutritive values differed significantly (p < 0.01) between different plant parts, except ME parameter. Results also indicated that J. fruticans due to its high tissue CP content is a valuable source of forage for livestock.